2021
DOI: 10.1002/cepa.1348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HST and WO Shear Connector Behaviour in Composite Slim Floor

Abstract: Composite steel‐concrete slim floor construction is an economical floor system proposing minimum floor depth and fast construction besides architecture requirements. In this system, the concrete slab is supported on the lower flange of the steel beam using either in‐situ or pre‐cast technique, which eliminates the use of the down‐stand beam, hence giving a flat look. Hollow steel tube (HST) shear connector is proposed to avoid premature failure that could occur in concrete and steel beam web when the web openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…e outcomes of FE were verified with the examination outcomes of one connector. e comparison demonstrated that the effective distance for three circular openings was about 250 mm, while it was noted to be nearly 300 mm for squared and rectangular openings [77,78].…”
Section: Effect Of the Opening Shapementioning
confidence: 99%
“…e outcomes of FE were verified with the examination outcomes of one connector. e comparison demonstrated that the effective distance for three circular openings was about 250 mm, while it was noted to be nearly 300 mm for squared and rectangular openings [77,78].…”
Section: Effect Of the Opening Shapementioning
confidence: 99%